KONTRIBUSI UNIT USAHA DALAM MEWUJUDKAN PERPUSTAKAAN SEBAGAI PUBLIC SPHERE DI PERPUSTAKAAN UNISSULA – SEMARANG - Krismayani, Ika (BACA: Jurnal Dokumentasi dan Informasi, 2020)
This study aims to identify and analyze the contribution of business units in realizing the library as a public sphere in the Unissula library. Specifically, the business unit studied was the canteen in the Unissula library. The research method used in this research is descriptive qualitative research method. The results showed that the business unit (i.e. canteen) in the Unissula library was considered to be a place for the realization of public sphere for the users. The location of the canteen which is close to the services in the library makes users feel free to chat with other users on the sidelines of utilizing the existing services of the Unissula library. The design of the canteen by providing adequate tables and chairs also makes users comfortable in meetings, discussions and interactions with other users.